The Influence Of Age And Gender: Unveiling Key Moderators In Insurtech Adoption And Use Behavior - Firmansyah, Fatah Panji; Princes, Elfindah (UNIVERSITAS PAKUAN, 2017)
This study aims to analyze the factors influencing the adoption and use of insurtech applications in Indonesia using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. The key factors examined include Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions, along with additional variables such as Trust, Convenience, and Regulatory Expectancy. A quantitative method was employed, with data collected through a survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Performance Expectancy, Effort Expectancy, Social Influence, and Trust significantly influence users' behavioral intention to adopt insurtech applications, while Convenience significantly impacts use behavior but not intention. In contrast, Regulatory Expectancy shows no significant influence on either intention or use behavior. Additionally, age moderates the relationships between certain variables, such as Social Influence, Convenience, and Facilitating Conditions, with both intention and use behavior, whereas gender only moderates the relationship between Social Influence and behavioral intention. In conclusion, application performance, ease of use, and trust are critical factors driving insurtech adoption, while convenience is key to sustaining usage.